2012
DOI: 10.1063/1.3692749
|View full text |Cite
|
Sign up to set email alerts
|

Jets in quiescent bubbles caused by a nearby oscillating bubble

Abstract: An oscillating bubble near another (stationary) bubble can give rise to interesting interactions. Such a nonequilibrium (oscillating) bubble can create a jet in a smaller nearby (initially stationary) bubble as demonstrated in this study both experimentally and numerically. In the experimental study, a spark-generated bubble (through a short circuit with two electrodes) was generated near a stationary smaller bubble. In order to keep the millimeter-sized bubble stationary, it was trapped in a droplet of silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…The overall behavior of interaction between the bubble and the free surface is recorded by a high speed camera. The liquid jet on the free surface can be divided into three parts, thin jet, thick jet, and crown-like structure around the thick jet, similar to the results of spark generations [4,7]. We find that the thin jet on the center of surface depression is crucial for crown formation and different morphologies of the crown-like structure appear with altering the bubble depth.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…The overall behavior of interaction between the bubble and the free surface is recorded by a high speed camera. The liquid jet on the free surface can be divided into three parts, thin jet, thick jet, and crown-like structure around the thick jet, similar to the results of spark generations [4,7]. We find that the thin jet on the center of surface depression is crucial for crown formation and different morphologies of the crown-like structure appear with altering the bubble depth.…”
Section: Introductionsupporting
confidence: 68%
“…This shape evolution was reconstructed well in theoretical simulations [3][4][5]. In addition to the bubble, a liquid jet was seen to burst out from the free surface, and for a certain bubble depth, there emerged a thin jet followed by a markedly thicker jet and a circular crown-like jet perfectly connected on the shoulder of the thick jet transited to the thin jet [4,7].…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…They inferred that the dominant interaction mechanism between the bubbles is due to the mutual interaction between the bubbles. Pain et al [9] conducted experiments * badarinath@iith.ac.in to illustrate the interaction of a stationary bubble with an oscillating bubble and found that this interaction leads to a jet in the stationary bubble with a velocity up to 250 m s −1 . Here, the stationary bubble was trapped inside a droplet before creating the oscillating bubble.…”
mentioning
confidence: 99%